RELATIONSHIP BETWEEN PLANT BIODIVERSITY AND CARBON STOCKS IN EVERGREEN BROAD-LEAVED FORESTS IN THE CENTRAL HIGHLANDS - Van Hop, Nguyen; Van Quy, Nguyen; Huu Quoc, Bui; Thi Luong, Nguyen (Journal of Forestry Science and Technology, 2021)
Forest ecosystems encompass many functions formed by many relationships between abiotic and biotic factors, with plant diversity and carbon stocks being the most important components. Using the plant diversity indices, and biomass functions based on 97 sample plots (OTC) of 500 m2 (25 m x 20 m) correlation analysis and multivariable regression were used to exploring the relationship between plant biodiversity and carbon stock in the evergreen broad-leaved forest in the Central Highlands. Studies have shown that the total carbon stock depends on the forest state and ranges from 38.93 ± 13.15 tons C/ha to 120.70 ± 32.93 tons C/ha. The results of the diversity indices Simpson (Cd), Shannon-Wiener (H'), Pielou (J'), and Magarlef (d) showed a moderate diversity of the forest states. There was a negative but weak relationship between the carbon stock and the Pielou index (J'). However, there was no statistically significant correlation between Species richness (S), Abundance (A), Simpson (Cd), Shannon-Wiener index (H'), Magarlef (d), and carbon stocks. Therefore, it pointed out that improving the carbon content of forests cannot guarantee the preservation and promotion of plant biodiversity. Preserving plant diversity should therefore be a priority in forest resource management. With the results obtained, the article contributes to creating a robust scientific basis and helping managers plan and develop strategies for the conservation and development of forest capital in the study area.